Polymorphism and Association of DMA Gene with Total IgY Concentration and ND Antibody Titer in IPB-D2 Chicken Line - D. Lestari; S. Murtini; N. Ulupi; C. Sumantri (Tropical Animal Science Journal, 2022)
The DMA (DM α chain) gene, a member of non-classical MHC class II plays an important role in the process of presenting antigen peptides by producing DM protein. This study aimed to identify the polymorphism of DMA gene and their associations with disease resistance traits such as total IgY concentration and ND antibody titers in IPB-D2 chicken line. The total sample used was 101 chickens consisted of 81 IPB-D2 G0 chickens (53 female and 28 male) and 20 SENSI-1 chickens (15 female and 5 male). Blood samples were collected at 21 weeks old for genotyping, total IgY concentration analysis, and ND antibody titer analysis. SENSI-1 chickens were used as a comparison in the analysis of DMA gene polymorphism. The method for DNA polymorphism of DMA gene was direct-DNA sequencing. The total IgY concentration was analyzed using the indirect ELISA method, while the ND antibody titer used the HI test. Data were analyzed using GLM, genotypic, and haplotype mean values compared with t-test. The results showed that 4 SNPs were found, i.e., g.2328 G>A (exon 3), g.2503 A>G (intron 3), g.2612 G>A, and g.2686 G>A (exon 4). The SNPs of DMA gene were found polymorphic with three genotypes (GG, AG, and GG), and the expected SNP g.2503 A>G only had two genotypes (AA and GG). The g.2328 G>A was associated (p<0.05) with total IgY concentration. A combination of 4 SNPs formed 7 haplotypes. Haplotype 1 was associated with total IgY concentration (p<0.05), and haplotype 5 was associated with ND antibody titer (p<0.05). In conclusion, the g.2328 G>A mutation and haplotype 1 could be potentially recommended as a genetic marker for high total IgY concentration, and haplotype 5 could be potentially recommended as a genetic marker for ND antibody titer in IPB-D2 chicken line.